Range of motion - Berg, Elizabeth (New York : Random House, 1995)
In this exquisite, emotionally rich novel, New York Times bestselling author Elizabeth Berg offers a deeply satisfying story about the bonds of love and the balm of friendship. A young man named Jay lies in a coma after suffering a freak accident, and his wife, Lainey, is the only one who believes he will recover. She sits at his bedside, bringing him reminders of the ordinary life they shared: fragrant flowers, his children$1 (Bs drawings, his own softly textured shirt. When Lainey$1 (Bs faith in his recovery falters, she is sustained by two women, Alice and Evie, who teach her about the endurance of friendship$1 (Band the genuine power of hope. Filled with beautiful writing and truths about life, Range of Motion is hard to put down and impossible to forget. s
75397
Keywords: Coma -- Patients -- Fiction; Friendship -- Fiction; Medical novels; Love stories; Domestic fiction